Implementasi Teaching Factory Tata Busana pada Mata Pelajaran Pembuatan Busana Industri - Cahyaningrum, Nur; Sudjimat, Dwi Agus; Irianti, Agus Hery Supadmi (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
The preparation and implementation of teaching factory in the subject of making industrial clothing at SMKN 1 Turen. This research approach is Mix Methods with Exploratory sequential design, initial data collected through interviews, observation and documentation, then supported by quantitative data through questionnaires with 5 alternative answers. The planning and implementation process was studied from the perspective of teachers and stakeholders related to teaching factory, while the evaluation was studied in terms of students as a result of the teaching factory learning process using Kirkpatrick evaluation. Data analysis using N vivo. The results showed that the preparation and implementation stages were in accordance with the teaching factory guidelines. The results of the evaluation stage analysis describe that after learning the teaching factory model, students' skills and knowledge have increased significantly, as seen from the comparison of the average report card scores before and after the implementation of teaching factory learning.Persiapan dan Pelaksanaan Teaching Factory pad mata pelajaran Pembuatan Busana Industri di SMKN 1 Turen. Pendekatan penelitian ini adalah Mix Methods dengan exploratory sequential design, data awal dikumpulkan melalui wawancara, observasi dan dokumentasi, kemudian didukung dengan data kuantitatif melalui kuesioner dengan 5 alternatif jawaban. Proses perencanaan dan pelaksanaannya dipelajari dari sudut pandang guru dan pemangku kepentingan yang terkait dengan teaching factory, sedangkan evaluasinya dikaji dari segi siswa sebagai hasil dari proses pembelajaran teaching factory dengan menggunakan evaluasi Kirkpatrick. Analisis data menggunakan N vivo. Hasil penelitian menunjukkan bahwa tahapan persiapan dan pelaksanaan sudah sesuai dengan pedoman teaching factory. Hasil analisis tahap evaluasi menggambarkan bahwa setelah pembelajaran model teaching factory keterampilan dan pengetahuan siswa mengalami peningkatan yang signifikan, terlihat dari perbandingan rata-rata nilai rapor sebelum dan sesudah pelaksanaan pembelajaran teaching factory.